2013
DOI: 10.1128/jcm.00719-13
|View full text |Cite
|
Sign up to set email alerts
|

Cell Extract-Containing Medium for Culture of Intracellular Fastidious Bacteria

Abstract: The culture of fastidious microorganisms is a critical step in infectious disease studies. As a proof-of-concept experiment, we evaluated an empirical medium containing eukaryotic cell extracts for its ability to support the growth of Coxiella burnetii. Here, we demonstrate the exponential growth of several bacterial strains, including the C. burnetii Nine Mile phase I and phase II strains, and C. burnetii isolates from humans and animals. Low-oxygen-tension conditions and the presence of small hydrophilic mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Although these microbes could be grown in their natural habitats (9), where effects such as cross-feeding (11) and microbe-host interactions (12,13) are present, some biological samples, such as clinical biopsies, are often limited in quantity. This makes it challenging to set up cultivation experiments in large scale with these native media, but creates opportunities for miniaturized methods.…”
mentioning
confidence: 99%
“…Although these microbes could be grown in their natural habitats (9), where effects such as cross-feeding (11) and microbe-host interactions (12,13) are present, some biological samples, such as clinical biopsies, are often limited in quantity. This makes it challenging to set up cultivation experiments in large scale with these native media, but creates opportunities for miniaturized methods.…”
mentioning
confidence: 99%
“…Singh et al developed an axenic liquid medium based on an extract of eukaryotic cells, allowing the growth of a broad spectrum of bacteria. The eukaryotic cell extract-based universal empirical medium, which was tested for culturing of C. burnetii as a proof of concept, supported the growth of other fastidious bacteria and putative bacterial bioter- rorism agents (120). Rapid growth (Ͻ72 h) was observed for T. whipplei, Yersinia pestis, Vibrio cholerae, Bacillus anthracis, Shigella dysenteriae, Brucella melitensis, Bordetella pertussis, and Bartonella henselae.…”
Section: Axenic Culture Media For Intracellular Bacteriamentioning
confidence: 99%
“…Moreover, colonies were observed on ACCM-2 agarose (372). More recently, Singh et al showed the exponential growth of C. burnetii in an empirical medium containing eukaryotic cell extracts (120). With the medium being refreshed every 2 days, low oxygen tension and the presence of small hydrophilic molecules and short peptides were critical for its growth.…”
Section: Axenic Culture Media For Intracellular Bacteriamentioning
confidence: 99%
See 2 more Smart Citations